Ethnic nationalism and income distribution in Malaysia - P. Chakravarty, Shanti; Abdul Hakim, Roslan (Palgrave Macmillan, 2005)
The need for the social inclusion of all ethnic groups is highlighted in discussions on development.That is an important point, but this paper urges caution about placing an exclusive focus on ethnicity in the formulation of policy.This argument is illustrated by way of an examination of the income distribution policies promulgated in Malaysia to improve the economic conditions of the Malay community after a series of race riots in 1969.